A Methods engineering study of Demex Rattancraft, Inc. - Dela Merced, Karen Grace T. (College of Engineering, 1994)
The study is divided into three parts namely : Methods Study, Work Measurement and Systems and Procedures. The group looked into the different steps and processes in the manufacturing of rattan furnitures from the delivery of the raw materials to the packaging for delivery to clients. The Framingm department was of primary concern. The present plant lay-out , the flow of operations, and arrangement of the machines and man in the workplace was taken into consideration. The working condition was also investigated by the group. A study on the efficiency of the workers and machines was made. The relationship of the efficiency of the components of production to the quality of the products and the duration of the production process will be discussed. The Systems and Procedure part of the study specifically looked into the existing procedures, policies, and forms used by the company. The revision of the forms was the main concern of our Systems and Procedures Study.